3D Hollow α‐MnO2 Framework as an Efficient Electrocatalyst for Lithium–Oxygen Batteries. Issue 10 (4th February 2019) - Bi, Ran; Liu, Guoxue; Zeng, Cheng; Wang, Xinping; Zhang, Lei; Qiao, Shi‐Zhang
Abstract: Lithium–oxygen (Li–O2 ) batteries are attracting more attention owing to their superior theoretical energy density compared to conventional Li‐ion battery systems. With regards to the catalytically electrochemical reaction on a cathode, the electrocatalyst plays a key role in determining the performance of Li–O2 batteries. Herein, a new 3D hollow α‐MnO2 framework (3D α‐MnO2 ) with porous wall assembled by hierarchical α‐MnO2 nanowires is prepared by a template‐induced hydrothermal reaction and subsequent annealing treatment. Such a distinctive structure provides some essential properties for Li–O2 batteries including the intrinsic high catalytic activity of α‐MnO2, more catalytic active sites of hierarchical α‐MnO2 nanowires on 3D framework, continuous hollow network and rich porosity for the storage of discharge product aggregations, and oxygen diffusion. As a consequence, 3D α‐MnO2 achieves a high specific capacity of 8583 mA h g −1 at a current density of 100 mA g −1, a superior rate capacity of 6311 mA h g −1 at 300 mA g −1, and a very good cycling stability of 170 cycles at a current density of 200 mA g −1 with a fixed capacity of 1000 mA h g −1 . Importantly, the presented design strategy of 3D hollow framework in this work could be extended to other catalytic cathode design for Li–O2 batteries. Abstract : A 3D hollow α‐MnO2 framework with a porous wall assembled by nanowires is prepared by a template‐induced hydrothermal reaction and subsequent thermal calcination. When tested as a cathodic catalyst for lithium–oxygen (Li–O2 ) batteries, the as‐prepared 3D α‐MnO2 achieves a higher round‐trip efficiency and better rate capacity and cycling stability.